Compositional heterogeneity may limit the usefulness of some commercial naphthenic acids for toxicity assays - West, C.; Jones, D.; Scarlett, Alan; Rowland, S. (2011)
Naphthenic acids are considered variously as monocarboxylic acids fitting the formula C nH 2n+zO 2 (where z is a zero or negative even integer), as only alicyclic (i.e. non-aromatic) monocarboxylic acids fitting this formula (z=0), or simply as those carboxylic acids occurring in petroleum products or crude oils that have been formed through biodegradation of hydrocarbons. Such acids are known constituents of the process-affected water associated with some expanding oil sands industries, of some immature and biodegraded crude oils, of produced water discharges from oil production platforms and are used as biocides and as components in the manufacture of steel radial tyres.As a result of these potential vectors of the acids into the environment, various naphthenic acid mixtures which are available commercially have been used for a range of toxicity studies. However, as some manufacturers make clear, but which is not often emphasised in the toxicity studies, a range of different quality naphthenic acids is produced commercially. It has been suggested previously, and we showed recently and elucidate further herein, that such commercial mixtures therefore sometimes contain toxic components other than carboxylic acids. For example, we identify herein by two-dimensional comprehensive gas chromatography-mass spectrometry, a range of C 0-6 alkylphenols in a batch of commercial naphthenic acids. Since these compounds are known toxicants, the contribution of such non-carboxylic acids, if any, to the toxicity attributed previously to the acids, should also be considered. This will be reflected in the concentrations and effective toxicities of such components. In order to establish the toxicity of the acids per se, assays of pure synthetic carboxylic acids of the type now known to be present in naphthenic acids from petroleum or oil sands may be more appropriate than tests of the toxicity of largely unknown, heterogeneous, mixtures. © 2011 Elsevier B.V.